2001
DOI: 10.1136/fn.84.3.f163
|View full text |Cite
|
Sign up to set email alerts
|

Background electroencephalographic (EEG) activities of very preterm infants born at less than 27 weeks gestation: a study on the degree of continuity

Abstract: Aims-To clarify the features of the background electroencephalographic (EEG) activities in clinically well preterm infants born at less than 27 weeks gestation and to outline their chronological changes with increasing postconceptional age (PCA). Methods-EEGs of clinically well premature infants born at less than 27 weeks gestation were recorded during the early postnatal period. The infants were separated into three groups according to their PCA at the time of EEG recording (21-22 weeks PCA, 23-24 weeks PCA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
53
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(60 citation statements)
references
References 23 publications
6
53
0
1
Order By: Relevance
“…The strong trends in EEG parameters in relation to CGA noted in our cohort are consistent with the results of other studies (16,17). Indeed, in our study, IBIs decrease with increased CGA (17).…”
Section: Permissive Hypercapnia and Eegsupporting
confidence: 82%
See 1 more Smart Citation
“…The strong trends in EEG parameters in relation to CGA noted in our cohort are consistent with the results of other studies (16,17). Indeed, in our study, IBIs decrease with increased CGA (17).…”
Section: Permissive Hypercapnia and Eegsupporting
confidence: 82%
“…Indeed, in our study, IBIs decrease with increased CGA (17). In our study, RP Δ shows slight increase until 30 wk gestational age possibly due to the decrease in IBI Articles Victor et al…”
Section: Permissive Hypercapnia and Eegmentioning
confidence: 60%
“…Several studies have shown that the duration of EEG bursts increase with gestational age and that IBI decrease with increasing gestational age in preterm infants 5 . This seems to be relevant also for the most immature infants, as shown by a study of 15 infants with EEG's recorded at 21 to 26 weeks postconceptional age 6 .…”
Section: Introductionmentioning
confidence: 99%
“…6,24,25 Similarly, the interburst interval, a surrogate measure of EEG discontinuity, was reported to decrease as GA increases. 5,6,24,25 Interestingly, in the present study, periods of continuous aEEG activity were found in preterm infants as early as 23 weeks of gestation.…”
Section: E64mentioning
confidence: 99%
“…Further, data on normal EEG patterns in extremely premature infants are still limited. 5,6 Recently, amplitude-integrated EEG (aEEG) provided by the cerebral function monitor (CFM), 7 a single-channel, time-compressed aEEG monitor, has gained widespread popularity as an alternative to conventional EEG monitoring in neonates. aEEG circumvents most of the problems of conventional EEG in this age group by generation of a compressed curve allowing continuous point-of-care monitoring for hours and a relative ease of application and interpretation.…”
mentioning
confidence: 99%